LEVERAGING ISLAMIC EDUCATION FOR SUSTAINABLE CHARACTER DEVELOPMENT TO AIMED FUTURE - Syadzali, Ahmad Alfi Nur (STIT Ibnu Rusyd Tanah Grogot, 2024)
This study aims to explore the implementation of character education based on Islamic values in elementary schools, focusing on the strategy of integrating these values in the educational process. This research is based on the importance of character education that is in line with Islamic teachings in forming a generation with noble character. The research method used is a qualitative approach with a case study type, involving the principal, deputy principal for curriculum, teachers, and students as the main informants. Data was collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model, which included data reduction, data presentation, and verification. The results of the study show that Islamic values are integrated into the curriculum, applied through active and participatory learning methods, supported by routine religious activities, and strengthened by the example of teachers and staff. Cooperation with parents also plays an important role in ensuring the consistency of character education at home and school. The results of this research lie in the provision of a model for the implementation of character education based on Islamic values that can be a reference for other schools in an effort to build a generation with strong character and noble character.